2018
DOI: 10.1155/2018/4147509
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Characteristics and Health Profile of the Elderly Seeking Health Care in Kampala, Uganda

Abstract: Aging entails health challenges globally, but pertinent data from low-income countries like Uganda remains scarce. A cross-sectional study was carried out at Mulago National Referral Hospital in Kampala, among 134 patients (38% men and 62% women) aged ≥60 years. Data was collected on sociodemographic characteristics, medical disorders, cognitive function, hearing handicap, and functional status, that is, Basic Activities of Daily Living (BADL) and Instrumental Activities of Daily Living (IADL). The participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 59 publications
0
19
1
Order By: Relevance
“…Most older people in Uganda (and generally in sub-Saharan Africa) are living with family members in multi-generational households with their children and grandchildren (Wandera et al, 2017), with younger generations looking after their elderly. However, without a reliable and consistent income, and high levels of chronic conditions in older adults, accessing healthcare is very limited and often restricted to basic medicines (Nawagi et al, 2018). Considering that the proportion of older adults is rising faster in LMIC, with the latest figures from 2015 of 46 million older adults in sub-Saharan Africa estimated to be more than triple by 2050 (United Nations, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Most older people in Uganda (and generally in sub-Saharan Africa) are living with family members in multi-generational households with their children and grandchildren (Wandera et al, 2017), with younger generations looking after their elderly. However, without a reliable and consistent income, and high levels of chronic conditions in older adults, accessing healthcare is very limited and often restricted to basic medicines (Nawagi et al, 2018). Considering that the proportion of older adults is rising faster in LMIC, with the latest figures from 2015 of 46 million older adults in sub-Saharan Africa estimated to be more than triple by 2050 (United Nations, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Oral hygiene (Lolita et al, 2015); (Lowe and Rossopoulos, 2018) Material 3 Oral hygiene (Dahm, Bruhn and Lemaster, 2015); (Chen et al, 2013) (Mahdizadeh and Solhi, 2018); (Miikkola et al, 2019) The Elderly is an age group that has shown a decline in organ function. The older age of a person causes a decrease in bodily functions due to aging which causes a decrease in physical strength.…”
Section: Resultsmentioning
confidence: 99%
“…Aging can cause the skin to become drier. In addition, the elderly also have problems with the skin and nail structures such as calluses and nails growing into the skin (Miikkola et al, 2019;Delgado et al, 2016).…”
Section: Personal Characteristic On Personal Hygiene and Health Carementioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, foods higher in calories, fat, cholesterol, and salt, and low in fiber‐containing foods (e.g., fruit, vegetables, and whole grain products) are linked with increased risk for diabetes, hypertension, coronary heart disease, cancer, and stroke, in adulthood (Leslie & Hankey, 2015; Phillips, 2003). Nawagi et al's (2018) study in Uganda revealed participants highly experiencing bone and joint pain which are frequently untreated. This was associated to eating low‐calcium diets with many being ignorant about the foods rich in bone building nutrients such as calcium and vitamin D. The second greatest reported medical condition relating to age was hypertension which was linked to poor nutrition and lifestyle issues.…”
Section: Resultsmentioning
confidence: 99%